2021
DOI: 10.1111/febs.16122
|View full text |Cite
|
Sign up to set email alerts
|

Structural and mechanistic insights into amyloid‐β and α‐synuclein fibril formation and polyphenol inhibitor efficacy in phospholipid bilayers

Abstract: Under certain cellular conditions, functional proteins undergo misfolding, leading to a transition into oligomers which precede the formation of amyloid fibrils. Misfolding proteins are associated with neurodegenerative diseases such as Alzheimer's and Parkinson's diseases. While the importance of lipid membranes in misfolding and disease aetiology is broadly accepted, the influence of lipid membranes during therapeutic design has been largely overlooked. This study utilized a biophysical approach to provide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…The acceleration of Aβ 40 aggregation in the presence of membrane surfaces is in agreement with previous studies 89 while an enhanced β-sheet formation of the related Aβ 42 peptide has been observed on oxidatively damaged surfaces, in particular. 69 The inhibition of U3.5 aggregation in the presence of POPG containing liposomes (POPG, POPC-POPG, 4:1) is also in agreement with our prior work when DMPG (1,2-dimyristoyl- sn -glycero-3-phospho-(1’-rac-glycerol)) lipid systems were studied.…”
Section: Resultssupporting
confidence: 92%
“…The acceleration of Aβ 40 aggregation in the presence of membrane surfaces is in agreement with previous studies 89 while an enhanced β-sheet formation of the related Aβ 42 peptide has been observed on oxidatively damaged surfaces, in particular. 69 The inhibition of U3.5 aggregation in the presence of POPG containing liposomes (POPG, POPC-POPG, 4:1) is also in agreement with our prior work when DMPG (1,2-dimyristoyl- sn -glycero-3-phospho-(1’-rac-glycerol)) lipid systems were studied.…”
Section: Resultssupporting
confidence: 92%
“…Native MS revealed the stoichiometry of binding of α-syn to nanodiscs as well as any smaller complexes formed. We used relatively low concentrations compared to prior studies, so we do not expect or observe significant fibril formation on the time scale of these experiments. ,, Higher-order oligomeric species were not detected, so we focus mainly on interactions between monomeric α-syn and the nanodisc bilayer.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Protein misfolding and aggregation are linked with a range of neurodegenerative disorders. However, the molecular basis of protein misfolding and toxicity in these diseases remains elusive, and there are no suitable therapeutic approaches to prevention. Recently, lipid membranes have been implicated in protein misfolding and disease etiology, but our current understanding of the interplay among misfolded oligomers, fibrils, and lipids is unclear. The lipid membrane composition, including headgroup and tail, can play an important role in misfolding protein aggregation kinetics and affect the morphologies of oligomers and fibrils. Because neuronal lipids change with age, the lipid environment may be an important driver of disease risk with increasing age …”
mentioning
confidence: 99%
“…2). 32,33 The three plant extracts tested significantly reduced both the rate and degree of αS fibril formation at a 1 : 1 ratio, however, purple sweet potato and blackberry extracts showed a concentration dependent decrease in fibril inhibition, with greatly reduced inhibition at a 10 : 1 ratio. In contrast, the lilly pilly extract exerted potent inhibitory activity across the three ratios tested and had comparable activity to EGCG (Fig.…”
Section: Resultsmentioning
confidence: 98%